Haq Al-Ujrah (hire right) in the light of Islamic jurisprudence and law - Abdulsoma, Thoarlim; Fauzi, Yusoh; Roslan, Ab Rahman; Ahmad Fauzi, Hassan; Mohammed Muneer'deen, Olodo Al-Shafi'i; Mohamad, Iman (2017)
Islam encourages seeking money and earning a living and control of spending habit based on morals. It forbids spending money through illegal means and has established rules for financial transactions on the basis of consent. Ujrah (hire) is considered the most important issue for an employee, and it is the focus of the relationship between him and his employer. Sharia and law clearly explain haqq al-ujrah (hire rights), an agreement between the employer and the employee for work done. Islamic scholars unanimously agree that the reward is either in cash, kind or benefit. However, scholars have different opinions regarding ujrah al-hijam (cupping hire) and taking reward for Quranic teaching. Reward is one of the pillars of contract, and the employer should pay without delay. Jurists also have different opinions regarding ijarah alnafaqah (feeding and clothing in exchange for work). The most important findings of this study is that haqq al-ujrah is in line with the stipulation of Islamic Jurisprudence and law. Islamic law has established rules for determining the wages of workers to ensure appropriate wages so that workers and their families may access basic needs and that equality between employers and workers may be achieved.